Characteristic and Attributes of the Modernization of Islam in Egypt - Firdaus Muhammad; Abdul Halim Bahri (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2022)
Egypt has a crucial and strategic role in the expansion of Islam throughout the world. The existence of Al-Azhar University as a center for Islamic studies is indicative of this. This article seeks to identify some of Egypt's most renowned Islamic reformers. This research consists of a historical literature review. According to the findings of the study, the resurrection of the Islamic modernizing movement and thought in Egypt was prompted by an awareness of the nation's intervention and even tyranny. This circumstance brought the Egyptians into contact with the technologically superior Western civilization. The formation of the fundamentals of civilizational modernity substantially bolsters the Egyptians' ability to advance in the arena of Islamic civilization in particular and the world at large. The resurgence of the modernization movement and ideas in Egypt was sparked by the emergence of a new power led by the Turkish-born Muhammad Ali Pasha. In an effort to reform, Muhammad Ali Pasha organized the Egyptian political and government system, expanded the influence of unity, constructed the education system, and absorbed as much knowledge from the outside as possible in order to educate Egyptians to study abroad in order to improve the intellectual quality of Egypt. The Islamic modernization movement and thought in Egypt has exhibited remarkable progress with the emergence of new ideas and movements in a variety of disciplines. Not only were they significant in Egypt, but also in the rest of the globe, particularly Islam. Among his followers were Raf'i al-Thahtawi, Jamaluddin al-Afgani, Muhammad Abduh, and Rashid Rida. The figure's primary objective is to make Egypt better capable of sustaining and expanding Islamization in other regions of the world.